Liver-Mediated Adaptive Immune Tolerance - Zheng, Meijuan; Tian, Zhigang (Frontiers in Immunology, 2019)
The liver is an immunologically-tolerant organ, equipped with the unique property of limiting hypersensitivity to food-derived antigens and bacterial products through the portal vein, and feasibly accepting liver allografts. The adaptive immune response is a major branch of the immune system that is responsible for inducing organ/tissue-localized and systematic responses against pathogens and tumors, while promoting self-tolerance. It has previously been reported that persistent liver infection with a virus or another pathogen typically results in liver tolerance, a unique feature of the liver. Due to the liver’s immunosuppressive microenvironment, hepatic adaptive immune cells become readily tolerogenic, promoting the death of effector cells and the ‘education’ of regulatory cells. The above mechanisms may result in the clonal deletion, exhaustion, or inhibition of peripheral T cells, which are key players in the adaptive immune response. It is believed that these tolerance mechanisms are responsible for almost all liver diseases. However, liver-mediated T cell dysfunction can be reversed through checkpoint immunotherapy or the modulation of hepatic innate immune cells. In this review, we focus on the mechanisms involved in hepatic adaptive immune tolerance, the liver diseases that arise as a result of this tolerance and how it can be overcome by therapeutic intervention. (200 words)